2020
DOI: 10.1097/01.aog.0000663336.99966.79
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting Rising Rate of No Prenatal Care in US Births Between 2012–2016 [27C]

Abstract: INTRODUCTION: To describe changes in rate of no prenatal care (PNC) in US between the years 2012–2016, and identify patient demographic and maternal medical risk factors for receiving no PNC. METHODS: Case-control study of US live births between 20–42 weeks gestation using vital statistics birth records. We analyzed maternal sociodemographic factors and medical characteristics as risk factors. Logistic regression estimated the influence of factors on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…A positive association between maternal education level and prenatal care services utilization was observed in the current study, with the association stronger among the low-income population. The overall positive association between maternal education and maternal health services utilization was consistent with previous studies conducted in both developing countries such as India [ 26 ] and Ethiopia [ 27 ] and developed countries such as Canada [ 28 ] and the United States [ 29 ]. A recent study conducted in the DRC also indicated that educational level was positively associated with having their first visit to antenatal care facilities within endemic malaria settings [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…A positive association between maternal education level and prenatal care services utilization was observed in the current study, with the association stronger among the low-income population. The overall positive association between maternal education and maternal health services utilization was consistent with previous studies conducted in both developing countries such as India [ 26 ] and Ethiopia [ 27 ] and developed countries such as Canada [ 28 ] and the United States [ 29 ]. A recent study conducted in the DRC also indicated that educational level was positively associated with having their first visit to antenatal care facilities within endemic malaria settings [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Antenatal services are predominantly attended by women with higher levels of education and from the middle-to-upper socioeconomic strata across various developed nations, namely Canada and the United States [62,63], South Korea [64], and Belgium [65]. Regardless of immigration background, women attaining higher levels of education typically exhibit greater health literacy and autonomy in navigating their pregnancy [66,67].…”
Section: Social Determinantsmentioning
confidence: 99%